Function and behaviour: use-wear evidence from Upper Paleolithic tools in southern Shanxi Province, North China - Hong Chen; Yiren Wang; Chun Chen (Documenta Praehistorica, 2016)
Lithic use-wear analysis has become a principal approach for interpreting the function of stone tools and inferring human behaviour. This study presents the results of use-wear analysis on lithic tools excavated from the Upper Paleolithic sites of Xiachuan and Chaisi in the southern part of Shanxi Province, North China. In this study, microblades and so-called core-like tools from these two sites were selected for examination by low-power techniques to identify their use patterns. The results suggest that approx. 30% of microblades might have been used mainly to process animal substances, and a lower percentage for vegetal substances. Based on the use-wear evidence, items classified as core-like tools should be regarded as microblade-cores, since they exhibit few traces of utilisation.